ISLAM PURITAN DAN OTORITAS AGAMA: DAKWAH RADIO BASS FM DI SALATIGA - Khoirin Nisai Shalihati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article aims to examine the religious authority in the preaching activities of the Bass FM Radio that developed in Salatiga, Central Java. The author uses a qualitative method with a phenomenological approach to obtain detailed, actual and in-depth information. The results showed the existence of authority, network and listeners of Bass FM Radio that still made radio as a solution for the deepening of knowledge about Islamic teachings. The Salatiga community does not yet have a comparison as a measure of Islamic da'wah radio in Salatiga. Radio Bass FM has followed technological developments by utilizing cyber media as an alternative medium for da'wah such as through the Facebook account bassFMsalatiga, Twitter @bassFMsalatiga, Instagram @RadioBassFM and YouTube Radio Bass FM Channel. This is the creativity of Bass FM in implementing the vision and mission of Islamic da'wah.